Faktor-Faktor yang Mempengaruhi Pengungkapan Risiko Perusahaan Perbankan Yang Terdaftar Di Bei - Jenni Meilody, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The objective of this research is to obtain empirical evidence about the effect of profitability, firm size and firm age to risk disclosure on banking companies listed in the Indonesia Stock Exchange (IDX) for the year 2014-2017. This study used a sample of 116 banking companies selected using purposive sampling method. The data used are secondary data in the form of financial statements. The statistical method used to test the research hypothesis is the multiple linear regression method in which the test is performed on panel data. The results of this research are firm age have positive effect on risk disclosure, meanwhile profitability and firm size has no effect on risk disclosure.